1986
DOI: 10.1210/endo-118-3-1180
|View full text |Cite
|
Sign up to set email alerts
|

Role of Central Serotonin Systems in the Stimulatory Effects of Ovarian Hormones and Naloxone on Luteinizing Hormone Release in Female Rats*

Abstract: The present experiments tested whether serotonergic neurons that innervate discrete areas of the hypothalamus are involved in the stimulation of LH release by ovarian hormones or the opiate antagonist naloxone in female rats. Ovariectomized rats received oil vehicle, estradiol benzoate (EB) alone, or EB followed by progesterone (P) 2 days later. Serotonin (5-HT) activity was assessed from the accumulation observed after the administration of the monoamine oxidase inhibitor pargyline. Two days after EB treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Previous studies have implicated catecholaminergic-, serotonergic-, GABAergic, opioid peptidergic, and LHRH neurons in the actions of circulating gonadal ste roids on the central nervous system [4,[14][15][16][17]. In the present study, in all three experimental groups, sections double-immunostained for PR and LHRH showed nei ther co-localization o f the two antigens in the same neu rons nor synaptic connections between LHRH-immunore active axons and PR-containing neurons.…”
Section: Resultssupporting
confidence: 52%
“…Previous studies have implicated catecholaminergic-, serotonergic-, GABAergic, opioid peptidergic, and LHRH neurons in the actions of circulating gonadal ste roids on the central nervous system [4,[14][15][16][17]. In the present study, in all three experimental groups, sections double-immunostained for PR and LHRH showed nei ther co-localization o f the two antigens in the same neu rons nor synaptic connections between LHRH-immunore active axons and PR-containing neurons.…”
Section: Resultssupporting
confidence: 52%
“…Addi tional studies in monkeys demonstrated that the concentration of p-endorphin in the hypo physeal portal blood draining the hypothala mus varies with different stages of the men strual cycle and is suppressed by ovariectomy but is increased by estrogen and progesterone replacement [10][11][12], Dupont et al [13] demonstrated a stimu latory effect of estradiol on Met-enkephalin levels in the nucleus interstitialis striae terminalis and in the medial and lateral preop tic nuclei of ovariectomized rats. It has been suggested that this effect may be due to es tradiol acting directly on the opiatergic neu rons in the hypothalamus with possible alter ations in the diurnal rhythm of serotonin activity [14,15]. This suggests that serotonin may play a role in regulating the circadian rhythm of the opiatergic pathways in the hy pothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulatory effect appears to reside in a system originating in the dorsal raphe nucleus (DRN) and terminating in the pre-optic area (POA) and median eminence (ME) [16, 17, 18, 19], but this system is only active in the presence of oestrogen [20, 21]. This is based on a wide variety of experiments including electrical stimulation and lesions of the DRN [17, 21]and noting a positive correlation in 5-HT activity and LH release in the three areas mentioned above (DRN, POA and ME) in both intact proestrous rats and ovariectomised rats primed with gonadal steroids that induce an LH surge (DRN [22, 23]; POA [19, 23, 24]; ME [25, 26]).…”
Section: Discussionmentioning
confidence: 99%
“…This is based on a wide variety of experiments including electrical stimulation and lesions of the DRN [17, 21]and noting a positive correlation in 5-HT activity and LH release in the three areas mentioned above (DRN, POA and ME) in both intact proestrous rats and ovariectomised rats primed with gonadal steroids that induce an LH surge (DRN [22, 23]; POA [19, 23, 24]; ME [25, 26]). Pharmacological evidence in vivo [28, 29]and in vitro [30, 31]also supports the stimulatory role of 5-HT in regulating LH release.…”
Section: Discussionmentioning
confidence: 99%